IMPLEMENTASI KONSEP BENEFICIAL OWNER ATAS PEMANFAATAN TAX TREATY INDONESIA-BELANDA (STUDI SENGKETA PAJAK TERKAIT PEMBAYARAN BUNGA) - Ardianyah, Ardianyah (IBLAM LAW REVIEW, 2021)
The Indonesia-Netherlands Tax Treaty is widely used by multinational corporations to avoid tax. The most crucial matter is how to determine the beneficial owner status, which is one of the requirements in the use of the Tax Treaty between Indonesia and the Netherlands. The main issue that becomes a problem is that the definition of beneficial owner is not clearly regulated in the Tax Treaty between Indonesia and the Netherlands. Therefore, disputes regarding the determination of the beneficial owner often occur. The attitude of judges in Indonesia on this matter is inconsistent. In certain decisions, the judge uses the principle of Substance Over Form and overrides formal evidence in the form of a Domicile Certificate. However, in another decision, the judge views the Domicile Certificate (SKD) as a reference without considering substantive facts. In another ruling, the judge used Dutch law to determine the beneficial owner status and override domestic legal provisions